FRONTEIRA, IMIGRANTE E PATRIMÔNIO CULTURAL: DESAFIOS DE GESTÃO COM BASE EM METODOLOGIAS DO CIRCUITO DE APOIO AO IMIGRANTE EM CORUMBÁ, MS, BRASIL - Wanessa Pereira Rodrigues (2021)
This thesis is a result of my experience living in the border, some concerns about my professional performance and experience accumulated near the cultural communities in Corumbá and Ladário, in which I could consider the difficulties, necessities and strategies adopted by them to maintain their cultural practices. The main purpose of this research was applying and transferring techniques of identification of cultural representative goods to the distinctive social groups, which are plausible to be recognized and protected as Corumbá´s Cultural Heritage. We believe there is a high level of complexity regarding to the presented theme in this project (border, immigrants, culture, cultural heritage). From the point of view of nature, it is an applied research, since it is oriented to generate practical appliance toward solving specific problems and involving local interests. During the bibliographical review some analyzed studies allowed an establishment of adjustments aiming the application of feasible procedures in the context of the local reality. The identification of cultural heritage was participatively, involving the community, through the construction of Affective Maps, made by students of five educational institutes in Corumbá-MS. The results obtained were: elaboration of a handout with all patrimonial goods already administratively registered in a way that teachers from the education network access this information and are able to work with patrimonial education in class; the cultural elements pointed in these affective maps generated a repport which was handed to Corumbá´s cultural management institution also to the Cultural Politics Concil, providing basis to possible registration or safeguard processes of cultural heritage; yet futher research is needed in order to understand and identify senses and values that are constantly produced as well as reworked by the communities involved.